Yield performance of 14 novel inter‐ and intra‐species Miscanthus hybrids across Europe. Issue 4 (30th January 2023) - Awty‐Carroll, Danny; Magenau, Elena; Al Hassan, Mohamad; Martani, Enrico; Kontek, Mislav; van der Pluijm, Philip; Ashman, Chris; de Maupeou, Emmanuel; McCalmont, Jon; Petrie, Gert‐Jan; Davey, Chris; van der Cruijsen, Kasper; et al.
Abstract: Miscanthus, a C4 perennial rhizomatous grass from Asia is a leading candidate for the supply of sustainable biomass needed to grow the bioeconomy. European Miscanthus breeding programmes have recently produced a new range of seeded hybrids with the objective of increasing scalability to large acreages limited by current clonal propagation. For the EU‐GRACE project, new replicated field trials were established in seven locations across Europe in 2018 with eight intraspecific M. sinensis hybrids ( sin  ×  sin ) and six M. sacchariflorus  ×  M. sinensis ( sac  ×  sin ) from Dutch and UK breeding programmes, respectively, with clonal Miscanthus  ×  giganteus. The planting density of the sin  ×  sin was double that of sac  ×  sin (30, 000 & 15, 000 plants ha −1 ), creating commercially relevant upscaling comparisons between systems. Over the first 3 years, the establishment depended on location and hybrid. The mature sin  ×  sin hybrids formed tight tufts of shoots up to 2.5 m tall which flower and senesce earlier than the taller sac  ×  sin hybrids. Following the third growing season, the highest yields were recorded in Northern Italy at a low altitude (average 13.7 (max 21) Mg DM ha −1 ) and the lowest yielding was on the industrially damaged marginal land site in Northern France (average 7.0 (max 10) Mg DM ha −1 ). Moisture contents at spring harvest were lowest in Croatia (21.7%) and highest in Wales, UK (41.6%). Overall, lower moisture contents at harvest, which are highly desirable for transport, storage and for most end‐use applications, were found in sin  ×  sin hybrids than sac  ×  sin (30% and 40%, respectively). Yield depended on climate interactions with the hybrid and their associated planting systems. The sin  ×  sin hybrids appeared better adapted to northern Europe and sac  ×  sin hybrids to southern Europe. Longer‐term yield observations over crop lifespans will be needed to explore the biological (yield persistence) and economic costs and benefits of the different hybrid systems. Abstract : Miscanthus is a leading candidate for the supply of sustainable biomass. Breeding programmes have recently produced the first range of seeded hybrids to increase scalability. We established eight intraspecific M. sinensis hybrids and six M. sacchariflorus  ×  M. sinensis hybrids including commercial clonal Miscanthus  ×  giganteus at seven sites across Europe with marginal land. The highest yields were recorded in Northern Italy and the lowest on industrially damaged land in Northern France. Yield depended on climate interactions with the hybrid, with the sinensis hybrids better adapted to northern Europe.